Photoplethysmography-documented atrial fibrillation in the first week after catheter ablation is associated with lower success rates - Manninger, Martin; Hermans, Astrid N. L.; Caracioni, Andrei-Antonio; Rohrer, Ursula; Eberl, Anna-Sophie; Vernooy, Kevin; Zirlik, Andreas; Linz, Dominik; Scherr, Daniel (Frontiers in Cardiovascular Medicine, 2023)
Aims: To test the feasibility of postprocedural photoplethysmography (PPG) rhythm telemonitoring during the first week after atrial fibrillation (AF) ablation and its predictive value for later AF recurrence. Methods: PPG rhythm telemonitoring during the first week after the ablation procedure was offered to a total of 382 consecutive patients undergoing AF ablation. Patients were instructed to perform 1 minute PPG recordings by a mobile health application 3 times per day and in case of symptoms. Clinicians assessed the PPG tracings via a secured cloud and the information was remotely integrated into the therapeutic pathway via teleconsultation (TeleCheck-AF approach). Results: 119 patients (31%) agreed to perform PPG rhythm telemonitoring after ablation. Patients included in the TeleCheck-AF approach were younger compared to those who declined participation (58±10 vs. 62±10 years, p<0.001). Median follow up duration was 544 (53-883) days. 27% of patients had PPG tracings suggestive of AF in the week following the ablation. In 24% of patients, the integration of PPG rhythm telemonitoring resulted in a remote clinical intervention during teleconsultation. During follow-up of one year, 33% of patients had ECG-documented AF recurrences. PPG recordings suggestive of AF in the week after ablation were predictive of late recurrences (p<0.001). Conclusion: PPG rhythm telemonitoring during the first week after AF ablation is feasible and was often triggering clinical interventions. Due to its high availability, PPG-based follow-up actively involving patients after AF ablation may close a diagnostic and prognostic gap in the blanking period and increase active patient-involvement.